DIAGNOSIS AND EVALUATION OF E-LEARNING QUALITY DIMENSIONS: AN EXPLORATORY STUDY - Farsat Shaban; Dilgash Qadir M. Salih; Waleed Al-Zaidi, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2021)
The aim of this study is to diagnose and evaluate e-learning quality dimensions (content, accessibility, quality of system used, evaluation, and feedback) from the students prospective in Iraqi institutes and universities after the e-learning system was implemented due to the emergence of the Corona pandemic (covid19) at the beginning of 2020. The study is based on the following question: Are the dimensions of e-learning quality available in Iraq? Knowing the answer to this question is considered a contribution of the current study because there are no previous studies that addressed the topic. The theoretical part of the research relied on articles that have been published in high-quality journals. As for the data of the practical part, it was obtained through the electronic questionnaire. The number of received forms reached (1016) forms. The study reached a conclusion that the weak implementation of e-learning quality dimensions in Iraqi higher education institutions. The study recommended Iraqi higher education institutions pay more attention to all dimensions of e-learning.